Transforming primary education: balancing social skills and academic achievement through global inquiry-based learning models - Seprie,; Wuryandani, Wuri; Muthmainah, (Frontiers in Education, 2025)
IntroductionThis study explores the impact of the Inquiry-Based Learning (IBL) model on enhancing social skills and academic performance among primary education students across various international settings. Amid the growing demand for 21st-century competencies, IBL offers a pedagogical approach that fosters both cognitive and interpersonal development.MethodsA qualitative meta-analysis was conducted using the Computer-Assisted Qualitative Data Analysis Software (CAQDAS), specifically NVivo 12 Plus. The study systematically reviewed and analyzed purposively selected literature on IBL implementation in countries such as Finland, Australia, Singapore, and the United States.ResultsThe analysis indicates that IBL significantly enhances students’ social skills—particularly collaboration, communication, and empathy—while also promoting academic engagement and performance. Success in IBL implementation is closely associated with flexible curriculum policies, as observed in Finland and Australia. In contrast, more rigid, assessment-driven systems present barriers to effective adoption.DiscussionThe findings highlight the critical roles of curriculum flexibility, teacher facilitation, and digital integration in optimizing IBL practices. To maximize the benefits of IBL, the study recommends embedding IBL more fully into national curricula, providing targeted teacher training, and expanding access to digital learning tools. These steps are essential for equipping students with the critical thinking, autonomy, and interpersonal competencies required in the globalized 21st-century context.